2006
DOI: 10.1086/505166
|View full text |Cite
|
Sign up to set email alerts
|

Stellar Populations in the Nuclei of Late‐Type Spiral Galaxies

Abstract: As part of an ongoing effort to study the stellar nuclei of very late-type, bulgeless spirals, we present results from a high-resolution spectroscopic survey of nine such nuclear star clusters, undertaken with VLT/UVES. We fit the spectra with population synthesis models and measure Lick-type indices to determine mean luminosity-weighted ages, which range from 4.1 × 10 7 to 1.1 × 10 10 years and are insensitive to assumed metallicity or internal extinction. The average metallicity of nuclear clusters in late-t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

31
277
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 211 publications
(311 citation statements)
references
References 78 publications
31
277
2
1
Order By: Relevance
“…A comparable result has also been deduced for 9 NCs of very late type bulgeless spirals by Walcher et al (2006) by means of a high-resolution spectroscopic survey with the VLT Ultraviolet and Visual Echelle Spectrograph (UVES). Genzel et al (2003), in their study of the stellar cuspy distribution around the supermassive black hole (SBH) in the Galactic center, found that the K-band luminosity function of the local NC (within 9 00 of Sgr A Ã ) resembles that of the large-scale Galactic bulge, but shows an excess of stars at K s 14.…”
Section: Introductionsupporting
confidence: 75%
“…A comparable result has also been deduced for 9 NCs of very late type bulgeless spirals by Walcher et al (2006) by means of a high-resolution spectroscopic survey with the VLT Ultraviolet and Visual Echelle Spectrograph (UVES). Genzel et al (2003), in their study of the stellar cuspy distribution around the supermassive black hole (SBH) in the Galactic center, found that the K-band luminosity function of the local NC (within 9 00 of Sgr A Ã ) resembles that of the large-scale Galactic bulge, but shows an excess of stars at K s 14.…”
Section: Introductionsupporting
confidence: 75%
“…Studies have shown that star formation in nuclear star clusters continues until the present day (Walcher et al 2006). Observations of nuclear clusters in edge-on spirals reveal that young stars are located in flattened disks (Seth et al 2006(Seth et al , 2008b.…”
Section: Introductionmentioning
confidence: 99%
“…NSCs are the densest known star clusters in the Universe. Most NSCs contain a mixed stellar population with signs of repeated episodes of star formation (Walcher et al 2006). Recent research suggests that there exists a Appendices are only available in electronic form at http://www.aanda.org…”
Section: Introductionmentioning
confidence: 99%